New radio-loud QSOs at the end of the Re-ionization epoch. Issue 2 (16th December 2022) - Ighina, L; Caccianiga, A; Moretti, A; Belladitta, S; Broderick, J W; Drouart, G; Leung, J K; Seymour, N
ABSTRACT: We present the selection of high-redshift ( z ≳ 5.7) radio-loud (RL) quasi-stellar object (QSO) candidates from the combination of the radio Rapid ASKAP Continuum Survey (RACS; at 888 MHz) and the optical/near-infrared Dark Energy Survey (DES). In particular, we selected six candidates brighter than $S_{\rm 888\, MHz}\gt 1$  mJy beam −1 and mag( z DES ) < 21.3 using the dropout technique (in the i -band). From this sample, we were able to confirm the high- z nature ( z ∼ 6.1) of two sources, which are now among the highest redshift RL QSOs currently known. Based on our Gemini-South/GMOS observations, neither object shows a prominent Ly α emission line. This suggests that both sources are likely to be weak emission-line QSOs hosting radio jets and would therefore further strengthen the potential increase of the fraction of weak emission-line QSOs recently found in the literature. However, further multiwavelength observations are needed to constrain the properties of these QSOs and of their relativistic jets. From the discovery of these two sources, we estimated the space density of RL QSOs in the redshift range 5.9 < z < 6.4 to be 0.13$^{+0.18}_{-0.09}$ and found it to be consistent with the expectations based on our current knowledge of the blazar population up to z ∼ 5.